Intervensi Media Sosial dalam Pergeseran Aktivitas Jurnalistik Online di Malang - Sujoko, Anang; Larasati, Galuh Pandu (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2017)
This article aims to describe in detail the social media influence on a shift towards journalistic practices in Malang Raya. Through observation and in-depth interviews to journalists of Malang Voice, Surya Malang, Times Indonesia, and Campus Info, this study has concluded that there has been a shift in journalistic activities resulted from the rapid growth of social media, namely the way of news production and news dissemination, the way of understanding journalistic principles, and gatekeeping role. In this regards, social media has become a highly important part of newsgathering as a wider range of sources, references, ideas, and issues, as well as channels for disseminating news. With regard to the changes of journalistic principle meaning, journalistic objectivity has referred to authentication, verification has shifted to transparency, and gatekeeping role has changed to collaborative practices.